Deteriorating Hemostatic Functions of Adult Female Wistar Rats Mediated by Activities of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) – Piroxicam and Vitamin E (Nigerian Journal of Physiological Sciences, 2021)
Summary: The status of hemostatic parameters, are useful physiological markers of organ and tissue damage and dysfunction. This study investigated the effect of Piroxicam on some hemostatic parameters of albino Wistar rats. Twenty-four (24) female albino Wistar rats were used for this study, they were randomly divided into four (4) groups of six (6) rats each. Group A served as control, Group B and C were rats treated with 0.1 mg/kg and 0.2 mg/kg piroxicam while Group D served as 0.2 mg/kg piroxicam treated rats administered with Vitamin E. The experiment lasted for a period of 4 weeks, after which the rats were euthanized. Blood sample was collected for measurement of bleeding time, clotting time, fibrinogen level and platelets count. One-way ANOVA was used to compare, means and a p
Keywords: Hemostasis; NSAIDs; Piroxicam; Bleeding Time; Clotting Time; Fibrinogen